2020
DOI: 10.1111/jvim.15728
|View full text |Cite
|
Sign up to set email alerts
|

Transurethral cystoscopy in dogs with recurrent urinary tract infections: Retrospective study (2011‐2018)

Abstract: Background Urinary tract infections (UTIs) are common in female dogs and recurrent infections often require investigation by transurethral cystoscopy. Hypothesis/Objectives Describe the findings of transurethral cystoscopy in dogs presented for recurrent urinary tract infections (RUTI). Animals Fifty‐three client‐owned dogs with RUTI were included in the study. Methods Retrospective study. Data collected from medical records included signalment, clinical findings, bladder wall culture, cystoscopic, and histopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 33 publications
(75 reference statements)
1
12
0
2
Order By: Relevance
“…Even the presence of an intrapelvic bladder did not appear to have affected dog's long‐term post CLA continence scores, in accordance with some earlier studies, although this has more recently been reported as a factor contributing to urinary incontinence 7,24,37 . Vaginal defects or vaginal septum were not reported as commonly as previous studies, however this may reflect the retrospective nature of our study if some findings were not clearly reported 7,31,38 …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Even the presence of an intrapelvic bladder did not appear to have affected dog's long‐term post CLA continence scores, in accordance with some earlier studies, although this has more recently been reported as a factor contributing to urinary incontinence 7,24,37 . Vaginal defects or vaginal septum were not reported as commonly as previous studies, however this may reflect the retrospective nature of our study if some findings were not clearly reported 7,31,38 …”
Section: Discussionsupporting
confidence: 89%
“…Only two third of dogs in this study received antibiotics after laser ablation of EUs unlike previous studies, where all dogs received antibiotics following laser ablation of EUs 7 . Dogs received antibiotics only if clinical signs were associated with a positive bacterial culture, as per current clinical recommendations 31–33 . We estimated that, as previously reported, subclinical bacteriuria should not be treated as it does not account for infection and may play a protective role preventing colonization by more pathogenic bacteria 34–36 …”
Section: Discussionmentioning
confidence: 95%
“…These include certain endocrinopathies (eg, hyperadrenocorticism), chronic kidney disease, urolithiasis, poor motor function, aberrant anatomy, immunosuppression, portosystemic vascular anomalies, and the presence of invasive devices in the urogenital tract. [15][16][17][18][19][20][21][22][23][24][25]…”
Section: Introductionmentioning
confidence: 99%
“…The utility of uroendoscopy in dogs with recurrent urinary tract infection (rUTI) is less clear. In dogs with rUTI, nonspecific cystourethroscopic and vaginoscopic findings such as mucosal edema, lymphoid follicles and vestibulovaginal septal remnants were noted in 45/53 (85%) cases, but no comparisons were made between endoscopic and ultrasonographic findings in that study 4 . In addition, that study did not determine if these findings were clinically relevant or related to the LUTS for which the dog was being evaluated.…”
Section: Introductionmentioning
confidence: 94%
“…Cystourethroscopic anomalies are reported in 45/53 (85%) dogs evaluated for rUTI, however many of these abnormalities could be considered nonspecific (eg, bladder and urethral mucosal edema and lymphoid follicles) regardless of the severity, rather than a pertinent uroendoscopic finding that would likely alter case managment. 4,20 Common findings in cystourethroscopy include vestibulovaginal abnormalities, such as vestibulovaginal stenosis. The latter has been reported as a potential contributing comorbidity in dogs with rUTI but was not included as a pertinent finding in our study.…”
Section: Multiple Lower Urinary Tract Signsmentioning
confidence: 99%